Heritage Building Maintenance Practices: The Case of Muzium Diraja Kedah (MDK) - Adnin Surayya Mohd Nasir; Deraman, Rafikullah (Journal of Structural Monitoring and Built Environment, 2025)
Maintaining heritage buildings requires a well-structured maintenance management system to ensure their continued usability and cultural significance. The Muzium Diraja (MDK) in Alor Setar, Kedah, an important historical landmark, faces several maintenance-related challenges, including financial constraints, limited access to original building materials, and a constrained maintenance budget, which affect the effectiveness of ongoing maintenance activities. This study investigates the current maintenance practices adopted at the museum using a qualitative case study methodology. Information was obtained through in-depth interviews with seven key personnel selected through purposive sampling, representing conservation, development, monument-related agencies, and the Public Works Department (JKR). The analysis identifies critical weaknesses in several key aspects of maintenance management, including organizational structure, asset management, maintenance strategies, workforce capabilities, financial provision, and documentation practices. Based on these findings, the study proposes targeted improvement measures, including the adoption of a structured maintenance management system, the implementation of proactive and planned maintenance strategies, the enhancement of technical skills among maintenance personnel, sufficient financial allocation, and systematic record-keeping. These measures are intended to support the sustainable preservation of the Muzium Diraja Kedah and safeguard its heritage value for future generations.